Socioeconomic disparity in stage at cancer diagnosis among patients with type 2 diabetes in Dutch primary care: a cross-sectional study - Geertruida H De Bock; Gijs W D Landman; Nanne Kleefstra; Bert van der Vegt; Sabine Siesling; Klaas H Groenier; Jing de Haan-Du (BMJ Public Health)
Introduction Disparities in cancer stage appear to exist by socioeconomic status (SES) in the Netherlands. We evaluated the association of SES and cancer stage among patients with type 2 diabetes (T2DM) treated in primary care.Research design and methods This cross-sectional study linked data from the primary care Zwolle Outpatient Diabetes Project Integrating Available Care database for T2DM (n=71 648, 1998–2019) to a cancer registry and personal records database in the Netherlands. Only cancers (excluding all skin cancers) diagnosed after the onset of diabetes were included and grouped by stages (III–IV or 0–II). SES was estimated as low, intermediate or high based on postal codes and Dutch social research status scores. Logistic regression was performed, with stratification by sex and correction for age, body mass index, smoking, diabetes duration, glycaemic control and metformin use. ORs and 95% CI are reported.Results Of the 5087 males and 4021 females with any cancer, 50.1% and 53.7% had low SES, respectively. Compared with patients with high SES, the ORs for diagnosing cancer at stages III–IV in patients with low SES were 1.00 (95% CI 0.84 to 1.19) for males and 1.32 (95% CI 1.06 to 1.67) for females. However, the ORs varied by cancer type: breast, 1.46 (95% CI 0.90 to 2.39); male colorectal, 1.00 (95% CI 0.70 to 1.43); female colorectal, 1.72 (95% CI 1.06 to 2.77); prostate, 0.81 (95% CI 0.57 to 1.15); male lung, 1.06 (95% CI 0.62 to 1.80) and female lung, 2.56 (95% CI 1.32 to 4.95).Conclusions Among patients treated for T2DM in Dutch primary care, our data suggest the need to target females with low SES to decrease inequalities in the early detection of colorectal and lung cancer.